2018
DOI: 10.1139/gen-2017-0202
|View full text |Cite
|
Sign up to set email alerts
|

Identifying small RNAs derived from maternal- and somatic-type rRNAs in zebrafish development

Abstract: rRNAs are non-coding RNAs present in all prokaryotes and eukaryotes. In eukaryotes there are four rRNAs: 18S, 5.8S, 28S, originating from a common precursor (45S), and 5S. We have recently discovered the existence of two distinct developmental types of rRNA: a maternal-type, present in eggs and a somatic-type, expressed in adult tissues. Lately, next-generation sequencing has allowed the discovery of new small-RNAs deriving from longer non-coding RNAs, including small-RNAs from rRNAs (srRNAs). Here, we systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 38 publications
0
64
0
Order By: Relevance
“…In earlier studies we discovered cellular components related to the transcription machinery that have distinct embryogenesis expression or somatic expression during zebrafish development. We reported on 5S (26), 5.8S, 18S, and 28S (27), plus small-derived components from those molecules (28), as well as snoRNAs (25). As it is clear that in zebrafish oogenesis and early embryogenesis a different transcription machinery is employed, it is obvious to investigate other components of this system.…”
Section: Cataloguing the Zebrafish Snrnasmentioning
confidence: 99%
“…In earlier studies we discovered cellular components related to the transcription machinery that have distinct embryogenesis expression or somatic expression during zebrafish development. We reported on 5S (26), 5.8S, 18S, and 28S (27), plus small-derived components from those molecules (28), as well as snoRNAs (25). As it is clear that in zebrafish oogenesis and early embryogenesis a different transcription machinery is employed, it is obvious to investigate other components of this system.…”
Section: Cataloguing the Zebrafish Snrnasmentioning
confidence: 99%
“…In this manuscript, we presented the preliminary results of our initial gene-expression analyses of the non-coding RNA types involved in the zebrafish translation system, other than we previously reported on (Locati et al 2017a(Locati et al , 2017b(Locati et al , 2018Pagano et al 2019bPagano et al , 2019a. Alike rRNA (Locati et al 2017a(Locati et al , 2017b, snoRNA (Pagano et al 2019b), and snRNA (Pagano et al 2019a), the investigated tRNA, RNase-P and SRP-RNA all seem to have a maternal-specific variant.…”
Section: Resultsmentioning
confidence: 99%
“…This maternaltype 5S RNA variant is gradually replaced throughout embryonic development by a somatictype variant (Wegnez et al 1972;Brown et al 1977;Wormington and Brown 1983;Guinta et al 1986;Komiya et al 1986). Starting from this long-standing observation, our continuous studies reported in several manuscripts (Locati et al 2017a(Locati et al , 2017b(Locati et al , 2018Pagano et al 2019bPagano et al , 2019a show the existence of a specialized maternal-type translation system in zebrafish far beyond just 5S rRNA. One by one, we have revealed that also the translation-involved non-coding RNAs 5.8S, 18S, 28S, snoRNA, and snRNA are implicated in this maternal-type translation system ( Figure 1 and Table 1).…”
Section: Introductionmentioning
confidence: 90%
“…Notably, miRNA-like molecules interchangeably called small rDNA-derived RNAs or rRNA-hosted miRNA analogs (srRNAs or rmiRNAs) derive from precursor and mature rRNAs through poorly understood mechanisms ( Figure 2C) [5,6]. srRNA/rmiRNA generation is likely not due to random degradation but rather controlled processing that creates stable srRNA products, and may be Drosha-dependent or independent [6][7][8]. Functionally, rmiRNAs have been shown to bind AGO proteins and are implicated in the regulation of various metabolic and developmental pathways.…”
Section: Noncanonical Mirna Sourcesmentioning
confidence: 99%